Inhibitory Effect of Acetylcholine on Monoamine Oxidase A and B Activity in Different Parts of Rat Brain - Osman, Mohamed Y.; Osman, Hassan M.Y. (Arzneimittelforschung, 2008)
Acetylcholine (CAS 60-31-1, ACh), which is similar in its chemical structure to the carbamate aldicarb, was found to inhibit brain monoamine oxidase isoenzymes, namely MAO-A and B. The effect of ACh on both isoenzymes extracted from the whole brain of male albino rats and its different parts (frontal cortex, basal ganglia, cerebellum, pons and medulla oblongata) was studied.The results indicated that ACh inhibited MAO-A from the cerebellum and MAO-B from the basal ganglia more than MAO iso-enzymes from other brain parts. The inhibition was of the competitive type. It was also found that the enzyme inhibitor dissociation constants (Ki) and the affinity constants (Ki/Km) of MAO-A were higher than those of MAO-B.
Keywords: Acetylcholine, MAO isoenzymes inhibition, rat brain; Benzylamine; CAS 60-31-1; Monoamine oxidase, inhibitor; Serotonin